Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Komisi Pemilihan Umum (KPU) Kota Probolinggo - Fiqi Mahendra; Abdul Haris; Elok Dwi Vidiyastutik (Universitas Panca Marga, 2024)
This study aims to determine the effect of Work Motivation and Work Discipline partially, simultaneously, and to determine the dominant variable on Employee Performance at the General Election Commission Office of Probolinggo City. This type of research is a type of quantitative research with an associative approach. The population in this study were all employees, totaling 33 employees with a sampling technique that is saturated sample. Source of data used in this research comes from primary data and secondary data. data analysis methods in this study in the form of validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate the effect of Work Motivation and Work Discipline simultaneously has a significant effect on Employee Performance. The results of this study also indicate that Work Motivation partially has a significant effect on Employee Performance. And Work Discipline partially has a significant effect on Employee Performance. The dominant influence in this study is Work Discipline..